2021
DOI: 10.1038/s41467-021-21383-1
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant anti-OX40 (MEDI6469) therapy in patients with head and neck squamous cell carcinoma activates and expands antigen-specific tumor-infiltrating T cells

Abstract: Despite the success of checkpoint blockade in some cancer patients, there is an unmet need to improve outcomes. Targeting alternative pathways, such as costimulatory molecules (e.g. OX40, GITR, and 4-1BB), can enhance T cell immunity in tumor-bearing hosts. Here we describe the results from a phase Ib clinical trial (NCT02274155) in which 17 patients with locally advanced head and neck squamous cell carcinoma (HNSCC) received a murine anti-human OX40 agonist antibody (MEDI6469) prior to definitive surgical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 49 publications
(64 reference statements)
5
69
0
1
Order By: Relevance
“…Oberst et al demonstrated that the human OX40L IgG4P Fc fusion protein (MEDI6383) subdues the Tregs function of immunosuppression by inducing the activation of T-cells in vitro and in vivo models [ 21 ]. The current trial of OX40 agonist demonstrated an increase in TILs and improvement in the patients with an adequate safety profile [ 22 ]. However, the effect of immune checkpoint blockade therapy on OSCC is limited and the subtypes within the TILs and expression of immune cell subtypes should be also taken into account [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oberst et al demonstrated that the human OX40L IgG4P Fc fusion protein (MEDI6383) subdues the Tregs function of immunosuppression by inducing the activation of T-cells in vitro and in vivo models [ 21 ]. The current trial of OX40 agonist demonstrated an increase in TILs and improvement in the patients with an adequate safety profile [ 22 ]. However, the effect of immune checkpoint blockade therapy on OSCC is limited and the subtypes within the TILs and expression of immune cell subtypes should be also taken into account [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Costimulatory receptors on T cells that have been targeted for immunotherapy of cancer include OX40, GITR and 4-1BB. Neoadjuvant anti-OX40 therapy in patients with head and neck squamous cell carcinoma led to increases of activated CD4 and CD8 T cells in both blood and tumors [ 51 ]. The initial results of therapy with an agonistic anti-GITR antibody indicates that it leads to reduction of regulatory CD4 T cells in both blood and tumors and would need to be combined with other immunotherapies, anti-PD-1 specifically, to attain clinical efficacy [ 52 ].…”
Section: Cd4 T Cells In Immune Checkpoint Blockade (Icb) Therapymentioning
confidence: 99%
“…However, the T cells made strong responses to the E6 and E7 proteins from human papilloma virus. Notably, these responses were exclusively found in the CD103 + CD39 + population of resident CD8 T cells (101), demonstrating that these cells are not restricted to mutated neoantigen reactivity. In B16 tumors in murine models, approximately half of the clonally expanded T cells in the tumor were reactive to the unmodified gp70 epitope that is shared in many murine tumors (43).…”
Section: Role Of Antigen In Tissue Retentionmentioning
confidence: 94%
“…However, in addition to neoantigens, there are an array of tumor-associated antigens (100) and in some cases viral antigens that can be effective targets for T cells. For example, in a recent clinical study in head and neck cancer, CD8 + T cells in the tumor did not make measurable responses to any of the mutated neoantigens that were present in the cancer cells (101). However, the T cells made strong responses to the E6 and E7 proteins from human papilloma virus.…”
Section: Role Of Antigen In Tissue Retentionmentioning
confidence: 95%